Fractional maximal and integral operators in variable exponent Morrey spaces - Wang, Panwang; Liu, Zongguang (Armenian Journal of Mathematics, 2022)
In this paper, we study the boundedness of the fractional maximal operator and fractional integral operator on the variable exponent Morrey spaces defined over spaces $(X,d,μ)$ of homogeneous type.